2012
DOI: 10.1007/s11095-012-0718-4
|View full text |Cite
|
Sign up to set email alerts
|

Human Pancreatic Polypeptide in a Phospholipid-Based Micellar Formulation

Abstract: Purpose Pancreatic polypeptide (PP) has important glucoregulatory functions and thereby holds significance in the treatment of diabetes and obesity. However, short plasma half-life and aggregation propensity of PP in aqueous solution, limits its therapeutic application. To address these issues, we prepared and characterized a formulation of PP in sterically stabilized micelles (SSM) that protects and stabilizes PP in its active conformation. Methods PP-SSM was prepared by incubating PP with SSM dispersion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
(48 reference statements)
2
27
0
Order By: Relevance
“…Examples of such studies include pancreatic polypeptide (PP), and neuropeptide Y (NPY) loaded micelles [147,148]. Banerjee et al encapsulated an endogenous peptide hormone, PP, in a phospholipid micellar formulation [147]. PP is secreted by F cells of the islets of langerhans of pancreas.…”
Section: Colloidal Delivery Systemsmentioning
confidence: 99%
“…Examples of such studies include pancreatic polypeptide (PP), and neuropeptide Y (NPY) loaded micelles [147,148]. Banerjee et al encapsulated an endogenous peptide hormone, PP, in a phospholipid micellar formulation [147]. PP is secreted by F cells of the islets of langerhans of pancreas.…”
Section: Colloidal Delivery Systemsmentioning
confidence: 99%
“…We have observed that various amphipathic peptide drugs undergo spontaneous association with SSM in aqueous media [20,33,[75][76][77][78][79]. Peptides such as vasoactive intestinal peptide (VIP), glucagon-like peptide 1 [GLP-1(7-36)] and gastric inhibitory peptides, associate most probably with the PEG region of PEGylated micelles, in view of the molecular net charge and relative hydrophilicity/hydrophobicity of these peptide candidates, rather than the more hydrophobic micelle cores as demonstrated in our previous fluorescence emission spectroscopic studies [76].…”
Section: Delivery Of Peptide and Protein Drugsmentioning
confidence: 99%
“…Peptides such as vasoactive intestinal peptide (VIP), glucagon-like peptide 1 [GLP-1(7-36)] and gastric inhibitory peptides, associate most probably with the PEG region of PEGylated micelles, in view of the molecular net charge and relative hydrophilicity/hydrophobicity of these peptide candidates, rather than the more hydrophobic micelle cores as demonstrated in our previous fluorescence emission spectroscopic studies [76]. Micelles stabilize the associated peptides against physical aggregation and hydrolytic degradation in vitro to increase their shelf stability in aqueous media [33,79,80]. When administered in vivo, SSM protects the associated peptides from plasma enzymes inactivation, bringing about enhanced and significantly prolonged biological activities (Fig.…”
Section: Delivery Of Peptide and Protein Drugsmentioning
confidence: 99%
“…Data were analyzed by volume and intensity-weighted distributions (31). Particle size determination assay was repeated after 3 days for all prepared formulations.…”
Section: Particle Size Determination Vlb-ssmmentioning
confidence: 99%